Предмет: Математика,
автор: madashapdzytrhfcjdf
Помогите решить пожалуйста!!!!
Упростите выражение: (х-2)( х во второй степени +3)-х в третьей степени
Ответы
Автор ответа:
1
(х-2)(х²+3)-х^3=х^3+3х-2х²-6-х^3=-2х²+3х-6
Автор ответа:
0
Ответ:
(х-2)(х²+3)-х^3=х^3+3х-2х²-6-х^3=-2х²+3х-6
Пошаговое объяснение:
Похожие вопросы
Предмет: История,
автор: hasamovalia
Предмет: Алгебра,
автор: neuven2000
Предмет: Химия,
автор: Iwanttoknowtheanswer
Предмет: Математика,
автор: kulebakin
Предмет: Математика,
автор: Аноним